Valorization of Oleuropein via Tunable Acid-Promoted Methanolysis - Cavaca, Lídia A. S. (2018)
The acid-promoted methanolysis of oleuropein was studied using a variety of homogeneous and heterogeneous acid catalysts. Exclusive cleavage of the acetal bond between the glucoside and the monoterpene subunits or further hydrolysis of the hydroxytyrosol ester and subsequent intramolecular rearrangement were observed upon identification of the most efficient catalyst and experimental conditions. Furthermore, selected conditions were tested using oleuropein under continuous flow and using a crude mixture extracted from olive leaves under batch. Formation of (−)-methyl elenolate was also observed in this study, which is a reported precursor for the synthesis of the antihypertensive drug (−)-ajmalicine.